International Migration of Nurses from South to North Amidst The COVID-19 Pandemic and Beyond: A Gain or A Drain - Hartiah Haroen; Jerico Pardosi (Jurnal Keperawatan Padjadjaran, 2022)
The complexity of health, social and economic problems caused by the COVID-19 pandemic demands rapid, adequate and effective responses. This includes the urgent response from the existing health system to provide high quality of care for infected persons. Unfortunately, the performance of health system in low-resource settings has been weakened prior to the COVID-19 pandemic. The current pandemic has posed more pressure to the health system including the health workforce security and availability with the isolation periods and lock-down scenarios for many low- and middle-income countries.Â  Nursing has been recognized as a profession with high global mobility. Nurses from the South (developing countries) would often migrate to the North (developed countries) due to security, better pay, and professional development, including working conditions. Nevertheless, aggressive recruitment of nurses from South amid the COVID-19 pandemic is considered unethical. Nurses as part of the essential health workforce are critically needed in their home countries. This editorial argues the benefits and disadvantages of nursesâ€™ migration from South to North. Several key sources from both scientific and grey literature were used in this editorial.